Infrared imaging investigation of temperature fluctuation and spatial distribution for a large laminated lithium–ion power battery. (April 2019) - Wang, Shixue; Li, Kaixiang; Tian, Yuan; Wang, Junyao; Wu, Yukang; Ji, Shan
Abstract: The present study investigates the thermal behaviors of a naturally cooled NCM-type LIB (LiNi1−x−y Cox Mny O2 as cathode) from an experimental and systematic approach. The temperature distribution was acquired for different discharge rates and Depth of Discharge (DOD) by the infrared imaging (IR) technology. Two new factors, the temperature variance ( T var 2 ) and local overheating index (LOH index), were proposed to assess the temperature fluctuation and distribution. Results showed that the heat generation rate was higher on the cathode side than that on the anode side due to the different resistivity of current collectors. For a low-power discharge, the eventual stable high-temperature zone occurred in the center of the battery, while with a high-power discharge, the upper part of the battery was the high–temperature region from the very beginning of discharge. It was found that the temperature variance ( T var 2 ) and local overheating index (LOH index) were capable of holistically exhibiting the temperature non-uniformity both on numerical fluctuation and spatial distribution with varying discharge rates and DOD. With increasing the discharge rate and DOD, temperature distribution showed an increasingly non-uniform trend, especially at the initial and final stage of high-power discharge, the heat accumulation and concentration area increased rapidly.